Conjugative plasmid DNA transfer in Helicobacter pylori mediated by chromosomally encoded relaxase and TraG-like proteins - Backert, Steffen; Kwok, Terry; König, Wolfgang (Microbiology, 2005)
One of the striking characteristics of Helicobacter pylori is the extensive genetic diversity among clinical isolates. This diversity has been attributed to an elevated mutation rate, impaired DNA repair, DNA transfer and frequent recombination events. Plasmids have also been identified in H. pylori but it remained unknown whether conjugation can contribute to DNA transfer between clinical isolates. To examine whether H. pylori possesses intrinsic capability for conjugative plasmid transfer, shuttle vectors were introduced into H. pylori containing an oriT sequence of the conjugative IncPα plasmid RP4 but no mobilization (mob) genes. It was shown that these vectors could stably replicate and be mobilized among clinical H. pylori strains. It was also demonstrated that traG and relaxase (rlx) homologues carried on the H. pylori chromosome were important for plasmid transfer. Primer extension studies and mutagenesis further confirmed that the relaxase homologue rlx1 in H. pylori encodes a functional enzyme capable of acting on the RP4 oriT. Furthermore, the findings of this study indicate that traG and rlx1 act independently of the previously described type IV secretion systems, including that encoded by the cag pathogenicity island and the comB transformation apparatus, in mediating conjugative plasmid DNA transfer between H. pylori strains. © 2005 SGM.
Created from Fastlane, Scopus look-up